2010
DOI: 10.1243/13506501jet739
|View full text |Cite
|
Sign up to set email alerts
|

Model-based virtual surface texturing for concentrated conformal-contact lubrication

Abstract: A model-based virtual texturing approach has been developed and applied to design, generate, 'test', and evaluate textured surfaces through numerical simulations. A series of studies on the numerical generation and performance evaluation of textured surfaces in a lubricated concentrated contact has been conducted, which includes (a) numerical generation of a large variety of textures considering possible geometric imperfections that exist in reality due to tooling design considerations and fabrication errors; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 27 publications
1
29
0
1
Order By: Relevance
“…Periodicity in the lubricant flow and topographical features ensure that homogenisation of the solutions obtained at the smaller scale produces data which represents the behaviour of the larger scale [8,9]. Solutions to the EHL problem which are deterministic by nature also remain the subject of a significant amount of recent research [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Periodicity in the lubricant flow and topographical features ensure that homogenisation of the solutions obtained at the smaller scale produces data which represents the behaviour of the larger scale [8,9]. Solutions to the EHL problem which are deterministic by nature also remain the subject of a significant amount of recent research [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Periodicity in the lubricant flow and topographical features ensure that homogenisation of the solutions obtained at the smaller scale produces data which represents the behaviour of the larger scale [8,9]. Solutions to the EHL problem which are deterministic by nature also remain the subject of a significant amount of recent research [10][11][12][13][14][15][16][17].Patir and Cheng [18] first developed a two-scale model to include the effects of surface topography in hydrodynamic lubrication known as the flow factors method. In this approach the terms of the Reynolds equation, which describes the lubricant flow in the contact under smooth surface assumptions [19], were multiplied by flow factors which include the homogenised effects of surface topography.…”
mentioning
confidence: 99%
“…Both deterministic (where the surface topographical features are fully described and resolved over the global domain) and homogenisation (where the flow about surface topographical features are solved independently and the results are applied to the global domain) models have been used by researchers to analyse bearings with surface texturing. Although CFD has the potential to comprehensively describe lubrication phenomena most research in this field to date remains focused on the use of the Reynolds equation, whether that is by deterministic [21][22][23][24] or homogenisation [11,[25][26][27][28] models. Few deterministic models have been developed which employ the Navier-Stokes equations [11,29] because of the large separation in scales between each local feature and the entire domain.…”
Section: Introductionmentioning
confidence: 99%
“…Mourier et al [11] has shown the importance of maintaining high pressure and lubricant viscosity inside dent to allow large outflow from the dent providing explanation for beneficial function of shallow indentations. Finally, further effect of dent geometry was studied by mixed EHL numerical model [12].…”
Section: Introductionmentioning
confidence: 99%